POTENSI TERKINI PERIODONTAL LIGAMEN STEM CELL SEBAGAI TERAPI REGENERATIF PERIODONSIUM: TINJAUAN PUSTAKA - Gustivanny Dwipa A; Sri Oktawati (Universitas Baiturrahmah, 2021)
Introduction: Regenerative therapies for periodontium aims to regenerate damaged periodontal tissue. Stem cell-based regenerative therapy may represent an effective therapeutic tool for periodontal regeneration. Periodontal ligament stem cells (PDLSCs) is a type of somatic stem cell that shows the potential to differentiate into several cell types and perform strong self-renewal. Therefore, PDLSCs are considered as a highly promising stem cell population for regenerative therapy in periodontium and need further knowledge regarding to the potential of using PDLSCs as a regenerative periodontium therapy. Literature Review: The periodontal ligament is a marker for stem cell, which is STRO-1. The STRO-1 marker is a colony-forming osteogenic precursor that can be isolated from bone marrow. The STRO-1 marker has the potential to be a phenotype of adipocytes, chondrocytes, and osteocytes. Markers of expression of STRO-1 from the surface of the periodontal ligament show that periodontal ligament cells have osteogenic precursors that can differentiate into osteoblasts. The potential multilineage differentiation of PDLSC including the adipogenic, chondrogenic, and osteogenic potential of PDLSC makes a promising cell source for cell-based regenerative periodontal therapy. Conclusion: The ability of PDLSCs in self renewal, multipotency, and stem cell immunomodulators, provides satisfactory results in the treatment of periodontal defects.